The Role of Language Tandems in the Internationalization of University Curricula - Tim Dittmann (Forum Neue Medien in der Lehre Austria, 2017)
The implementation and evaluation of innovative teaching concepts which promote intercultural competencies and foreign language skills, e.g. language tandems, are often underdeveloped at German universities. This outcome evaluation study investigated selected effects of participation in language tandems on the knowledge, skills and attitudes of participants. The hypothesis that language tandem participation fosters 'language self-efficacy, cultural intelligence, learner autonomy, and intrinsic goal orientation', was examined on a sample of 47 participants using pre-post-questionnaires. Results showed a significant improvement in participants' language self-efficacy and cultural intelligence.